THE JADIDS’ TRANSFORMATIVE ROLE IN THE EMERGENCE OF UZBEK MASS MEDIA - Dilfuza Muminovna Teshabayeva (Western European Studies, 2025)
This article offers a narrative reassessment of the Jadid movement’s pivotal role in shaping the early media landscape of Central Asia and establishing the foundations of modern Uzbek journalism. Drawing on open-access historical and scholarly sources, it examines how Jadid intellectuals strategically employed newspapers, journals, and print networks to advance educational reform, promote secular knowledge, and articulate emerging notions of national identity. The study highlights the Jadids’ innovative use of vernacular Turkic in print, their development of new journalistic genres, and their efforts to cultivate a reading public capable of participating in public debate. Despite facing censorship, financial limitations, and structural barriers under Russian imperial rule, their press initiatives generated an early public sphere and institutionalized media practices that influenced later Soviet and post-independence Uzbek media. By situating Jadid print culture within broader processes of modernization, the article underscores its enduring impact on the region’s intellectual and communicative development
Keywords: Jadidism; Uzbek journalism; early press